Magnetisation configuration in arrays of permalloy rectangles and its impact on magnetisation reversal. (15th September 2021) - Newton, P J; Devlin, N B; Masur, S M; Ghidini, M; Backes, D; Maccherozzi, F; Pacheco-Pumaleque, A A; Esqueche, M A González; Barnes, C H W
Abstract: The remanent domain structures of composite element magnetic barcodes have been imaged using photo-emission electron microscopy with contrast from x-ray magnetic circular dichroism (XMCD-PEEM) and analysed with reference to the results of micromagnetic simulations. The magnetisation configuration at the end of wide strips is found to be perpendicular to the majority magnetisation direction. This transitions to an incomplete rotation for nominal strip widths below 300 nm and is found to affect the mechanics of magnetisation reversal for nominal strip widths below 200 nm, owing to a difference in magnetisation orientation when an external magnetic field is applied that is just smaller than the magnetic coercivity of the structures and a corresponding change in reversal dynamics. This change in domain structure as strip width decreases is consistent with both the influence of shape anisotropy and with measurements of magnetic hysteresis. The magnetisation reversal characteristics of composite element structures are found to be dependent on the relative magnetisation configurations of neighbouring strips, which in turn are found to vary stochastically upon the application and removal of a magnetic field along the easy axis of the structure. It is found that the application of a canted field is necessary to ensure sharp, consistent magnetisation reversal of bits when writing a binary code. These results confirm that either improved lithography of narrower strips or non-rectangular elements would be necessary to further increase the number of individually programmable bits in a barcode.